Calculation models of beams with one-way connections - A. K. Yusupov; Kh. M. Muselemov; R. I. Vishtalov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The article considers the operational features of beam structures with one-way ties. Method. By studying the operational features of beam structure supports, analytical and graphical dependencies between beam displacements and their support reactions are derived. The properties of generalized functions are used to describe the nonlinearities that occur during structural deformations. Differential equations for transverse bending of beams are presented, taking into account nonlinearities and methods for their solution. Result. Design and calculation schemes have been developed that take into account the operation of beam structure supports, allowing us to obtain precise values of deflections and internal forces of sections on this basis, which ensures the necessary reliability of the structure. The results are given in the form of analytical expressions, graphs, and tables. Conclusion. Calculation models of beams with one-way connections can find wide application in the design of beam structures with supports with one-way connections.